Al-Musahamah Akad Mechanism In Joint-Stock Company: A Contemporary Study Of Share Diksi - Basrowi Basrowi; Pertiwi Utami (LPPM ISNJ Bengkalis, 2021)
The musyarakah al-musahamah agreement in Islamic stock transactions is a new thing in the capital market. As a result, investors in the issuer are less knowledgeable about the many forms of sharia products. The purpose of this study is to provide a deeper understanding of step by step and examples of the practice of al-Musahamah akad in the world of stocks. This research uses qualitative methods by becoming literature in contemporary fiqh studies and Islamic economics. The study of contemporary fiqh and Islamic economics is one of the reference materials that can be used to implement the al-musahamah akad in the practice of Islamic finance. The study results found that the study of modern fiqh and fatwas of the Syariah Council and several scholars allow the practice of the al-musahamah akad in the shariah stock business as long as it does not violate the harmony and requirements of sharia. Even though in practice the al-musyarakah akad in joint stock companies in Indonesia is not 100% by the principles of sharia and modern fiqh, due to the element of use as an objective of sharia and maqasid maslahah, it can be considered to improve existing mechanisms for the better in the future. Supporting previous research that explains the practice of syirkah al-musahamah, this depth research explores the process and practice of the al-musahamah akad in a joint-stock company.